2018
DOI: 10.1075/aral.18020.bur
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a framework for learning to teach English pronunciation in an Australian TESOL program

Abstract: A substantial number of studies have been conducted in various second language teacher education settings. Yet, evidence about the effectiveness of teacher preparation continues to be debated and research findings about the efficacy of preparing language teachers are still somewhat inconclusive. As a further complication, even though pronunciation has regained some of its prominence in second language teaching, only minimal understanding exists about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
1
6
0
1
Order By: Relevance
“…However, five student teachers chose not to implement communicative activities for three primary reasons: (1) the learner was not ready; (2) a lack of confidence in the teacher; and (3) unable to design communicative activities for certain features. This finding is in line with Burri (2016) and Buss (2017), who also found that controlled activities were favored more than less-controlled activities. This, however, could be attributable to the tutoring context, as six participants suggested communicative activities would be more suitable for a classroom setting.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, five student teachers chose not to implement communicative activities for three primary reasons: (1) the learner was not ready; (2) a lack of confidence in the teacher; and (3) unable to design communicative activities for certain features. This finding is in line with Burri (2016) and Buss (2017), who also found that controlled activities were favored more than less-controlled activities. This, however, could be attributable to the tutoring context, as six participants suggested communicative activities would be more suitable for a classroom setting.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, Burri and Baker (2020) followed up with five of Burri's (2016) participants who now had been working as ESL/EFL teachers for 1.5 to 2.5 years. Using data collected from the pronunciation pedagogy course and also narrative frames collected during their teaching experience, they found that the "participants' process of learning to teach pronunciation gradually developed over [time]" (p. 11), but that their learning trajectories were inconsistent after the course had ended.…”
Section: Second Language Teacher Training In L2 Pronunciation Pedagogymentioning
confidence: 99%
See 2 more Smart Citations
“…esim. Burri, Baker & Chen, 2018;Huensch, 2019;Uchida & Sugimoto, 2020). Pidämme tärkeänä myös suomalaista tutkimusta tästä aihealueesta.…”
Section: Johdantounclassified